2010
DOI: 10.2489/jswc.65.6.438
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate analysis of covariance to determine the effects of near-stream best management practices on nitrogen and phosphorus concentrations on a dairy farm in the New York Conservation Effects Assessment Project watershed

Abstract: Near-stream best management practices (BMPs), such as exclusionary fencing or cattle crossings, are often recommended to improve water quality, but quantification of their impacts is limited. Surface and subsurface processes in these near-stream areas impact the contribution of nitrogen and phosphorus to watercourses and the effectiveness of near-stream BMPs. To test the impact of the near-stream BMPs, groundwater samples from 30 piezometers and streamwater samples along two adjacent creeks (one control and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…The farm does not have any manure storage so the manure is generally handled and applied daily as a solid and milkhouse wastewater is sometimes added to it for its disposal. In the winter about eighty percent of the manure is spread on the valley bottom lands (average rate of 35 Soil samples taken in the field around the farm in 2004 showed that total P concentrations were above the levels that indicate of high P accumulation in the soil [12].…”
Section: Study Sitementioning
confidence: 99%
See 3 more Smart Citations
“…The farm does not have any manure storage so the manure is generally handled and applied daily as a solid and milkhouse wastewater is sometimes added to it for its disposal. In the winter about eighty percent of the manure is spread on the valley bottom lands (average rate of 35 Soil samples taken in the field around the farm in 2004 showed that total P concentrations were above the levels that indicate of high P accumulation in the soil [12].…”
Section: Study Sitementioning
confidence: 99%
“…The partial years sampled during this study had approximately normal precipitation levels [12]. The average precipitation during the growing season (May to September) and the non-growing season were 596 mm and 661 mm, respectively [46] …”
Section: Precipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…In "A multivariate analysis of covariance to determine the effects of near-stream best management practices on nitrogen and phosphorus concentrations on a dairy farm in the New York Conservation Effects Assessment Project watershed," Flores-Lopez et al (2010) demonstrated using paired field design that stream fencing with a width of 5 m (16 ft) and cattle crossing (same width) reduced annual soluble reactive P loading by 27%, but did not reduce NO 3 -N, probably due to large carbon availability from the dairy waste and saturated soils, which together facilitated denitrification.…”
Section: Land Treatmentmentioning
confidence: 99%